1998
DOI: 10.1038/sj.onc.1202004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased fibronectin expression in Met/HGF-mediated tumorigenesis

Abstract: The tyrosine kinase receptor Met and its ligand, hepatocyte growth factor (HGF)/scatter factor are involved in the etiology and progression of a number of human cancers. Coexpression of Met and HGF in mesenchymal cells increases the tumorigenic and metastatic potential of the cells. In the studies described here, we used di erential display screening to identify changes in gene expression that are initiated by Met/HGF, and that may lead to these phenotypes. We learned that Met/ HGF signaling resulted in greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…Recent studies using human mesangial cells have also demonstrated that HGF can suppress TGF-β1 expression induced by a high concentration of glucose [14]. HGF also represses TGF-β1 production [25,26]. Thus, in our study, it seems that HGF alters TGF-β1 regulation at multiple levels.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies using human mesangial cells have also demonstrated that HGF can suppress TGF-β1 expression induced by a high concentration of glucose [14]. HGF also represses TGF-β1 production [25,26]. Thus, in our study, it seems that HGF alters TGF-β1 regulation at multiple levels.…”
Section: Discussionsupporting
confidence: 69%
“…DAB2 is of particular interest since it suppresses signaling from the growth factor signal transduction pathway to AP-1 (33,104) and is down regulated in a variety of human tumors (11,23). Other known tumor suppressor genes, those for thrombospondin 1 (63,78), RECK (69,81,99), TIMP1 (77), IGSF4 (25), gremlin/ CKTSF1B1 (10), sFRP1 (49,98), IGFBP7/MAC25 (96), fibronectin 1 (52,73,101), STAT1 (38), and FAT (21), and some purported tumor suppressor genes, those for brush-1/WASF3 (87), TES (102), and WNT5A (39), are all down-regulated in Tif-Fos cells. The number of tumor suppressor genes that are down-regulated in Tif-Fos cells and their breadth of activities (ECM components, transcription regulators, signal transducers, and protease inhibitors) reflect the complexity of the invasion program and the many aspects of cell biology that are engaged during invasion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of FN in tumorigenesis and malignant progression has been highly controversial [7,8]. On the one hand, it has been reported that FN expression in tumor cells plays a tumor suppressive role to prevent tumor transformation and to halt their early progression [9]. On the other hand, abundant evidence reveals that FN provokes late stages of cancer metastasis and is associated with poor prognosis when endogenously expressed in tumor cells.…”
Section: Introductionmentioning
confidence: 99%